Síndrome Coronario Agudo: Índice Leucoglucémico para estratificación de riesgo en el Infarto Agudo del Miocardio - Cervantes-Coka, Manuel Antonio (Ciencia UNEMI, 2011)
Acute coronary syndrome is the term used to define initial operational clinical presentation of the patient and allows for early therapeutic conduct. According to the World Health Organization in 2009 Ischemic heart disease killed 15 million people in the world. In our environment it is one of the most common medical emergencies which has are of the more heterogeneous approaches due to the constant evolution in diagnostic and therapeutic tools. It has now become a focus of clinical research covered by most international literature. This article is presenting a retrospective research study which will be carried out at the Luis Vernaza Hospital in Guayaquil by the cardiology department, analyzing the population admitted with a diagnosis of acute myocardial infarction (AMI) in the last three years. The aim is to produce a prospective study to compare national data with those of international literature.